TINGKAT KECEMASAN PERAWAT DALAM MERAWAT PASIEN COVID-19 DI RUMAH SAKIT TK II UDAYANA DENPASAR - I Gede Yudiana Putra; Dedi Irwan Pamungkas (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
ABSTRACTBackground: The impact of the Covid-19pandemic has caused many losses, such as mental disorders such as anxiety. Anxiety is not only felt by the community, but also experienced by all health workers such as nurses, as the front line in dealing with Covid-19. One of the forms of anxiety shown is that in caring for Covid-19patients, nurses must wear protective clothing and N95 masks to avoid exposure to infection, the fear of being infected and infected triggers psychological problems experienced by nurses, where this can have a bad effect on the quality of care. Lack of focus on the mental health of health workers has the potential to disrupt and even turn off health services and will affect the handling of the Covid-19 pandemic. Methods: The research design used is descriptive. The population in this study were nurses who took care of Covid-19patients, totaling 30 respondents. The sampling technique used in this research is non-probability sampling, namely total sampling. The types of data collected in this study are primary data and secondary data. The instrument used is the HARS (Hamilton Anxiety Rating Scale) questionnaire. Data processed using the SPSS program were analyzed to determine the final score and determine the category of anxiety. Results: The results of this study obtained that most of the nurses' anxiety level was classified as severe anxiety as many as 26 respondents (86.7%). Gender characteristics are mostly female as many as 26 respondents (86.7%). The age characteristics of most respondents aged 36-45 years were 16 people (53.3%). and the characteristics of the final education of the majority of respondents with D3 Nursing education as many as 16 people (53.3%). Conclusion: The level of anxiety of nurses in treating Covid-19 patients at Level II Udayana Hospital is severe anxiety.Keywords: Covid-19, Nurse, Anxiety LevelABSTRAKLatar Belakang : Dampak dari pandemi Covid-19menimbulkan banyak kerugian seperti halnya gangguan mental seperti kecemasan. Kecemasan tidak hanya dirasakan oleh masyarakat saja, namun juga dialami seluruh tenaga kesehatan seperti perawat, sebagai garda terdepan dalam menangani covid-19. Salah satu bentuk kecemasan yang ditunjukan adalah dalam melakukan perawatan pada pasien covid 19 perawat harus mengenakan pakaian pelindung dan masker N95 untuk menghindari paparan infeksi, rasa takut tertular dan terinfeksi menjadi pemicu masalah psikologis yang dialami oleh perawat, dimana hal ini dapat memberikan efek buruk pada kualitas perawatan. Fokus perhatian yang kurang terhadap kesehatan mental tenaga kesehatan berpotensi mengganggu bahkan mematikan pelayanan kesehatan dan akan berpengaruh pada penanganan pandemi Covid-19. Metode : Desain penelitian yang digunakan ialah deskriptif. Populasi dalam penelitian ini adalah perawat yang merawat pasien covid-19 yang berjumlah 30 responden. Teknik sampling yang digunakan pada penelitian ini adalah nonprobality sampling yaitu total sampling. Jenis data yang dikumpulkan dalam penelitian ini adalah data primer dan data sekunder. Instrument yang digunakan adalah kuesioner HARS (Hamilton Anxiety Rating Scale). Data diolah menggunakan program SPSS dianalisis menentukan skor akhir dan menentukan katagori kecemasan. Hasil : Hasil Penelitian ini diperoleh tingkat kecemasan perawat sebagian besar tergolong kecemasan berat sebanyak 26 responden (86,7%). Karakteristik jenis kelamin sebagian besar berjenis kelamin perempuan sebanyak 26 responden (86,7%). Karakteristik umur sebagian besar responden usia 36-45 tahun sebanyak 16 orang (53,3%). dan karakteristik pendidikan akhir sebagian besar responden berpendidikan D3Keperawatan sebanyak 16 orang (53,3%). Kesimpulan : Tingkat kecemasan perawat dalam merawat pasien Covid-19 di Rumah Sakit Tingkat II Udayana adalah kecemasan berat.Kata kunci : Covid-19; Perawat; Tingkat Kecemasan